PROFIL PASIEN KANKER ENDOMETRIUM DI RSUP SANGLAH DENPASAR PERIODE AGUSTUS 2012 – JULI 2014 - Putu Pradnya Paramitha Dewi; I Nyoman Gede Budiana (E-Jurnal Medika Udayana, 2017)
Endometrial cancer occurs in the endometrium, the innermost layer of uterus, the cells grow uncontrollably, invade and damage nearby tissues. Sanglah Hospital as a referral hospital in the eastern part of Bali and Indonesia in the last decade hasn’t data on the incidence of endometrial cancer. The study was conducted to determine the incidence of endometrial cancer in Sanglah Hospital and other profiles associated with endometrial cancer.This study used a descriptive design retrospective data obtained from clinic obstetrics and gynecology and installation of medical records department of Sanglah hospital.The number of patients diagnosed with endometrial cancer period August 2012-July 2014 was found and have a complete profile as many as 26 cases. Based on the results of the study, the proportion of endometrial cancer compared with gynecologic cancer was 9.2% with the highest number of endometrial cancer patients in the age group 51-60 years (46.2%) having 3 children (30.8%) with a normal body mass index (42.3%) in stage III (38.5%) and had histopathology type is 65.4% of endometrioid adenocarcinoma. Some patients with endometrial cancer also found have a history of hypertension and diabetes mellitus. Concluded the incidence of endometrial cancer in elderly women with 3 children and normal body mass index in stage III with endometrioid adenocarcinoma histopathology type and few had history of hypertension and diabetes mellitus. The results of this study can be used as a basis for further research, promotes and preventive efforts for the community in order to improve survival in endometrial cancer. Keywords : Endometrial cancer, profile, Sanglah Hospital.